Integration of Qur'anic and Hadith Values in Evolution Learning: Innovation of Biology Modules Based on Faith Education - Syam, M Ikhsan; Falemu, Funke Aina; Hussain, Mufida Bello (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The purpose of this study is to develop a biological evolution module based on Qur'anic and Hadith values ​​to improve academic understanding, religious character, and learning guidance according to the principles of Muslim students' faith. Methodology: This study uses the Development research method with ADDIE research design. The research subjects consisted of 60 students of the Biology Education Department of UIN Alauddin Makassar, who were divided into two groups: experimental and control. Data collection techniques include interviews, questionnaires, and documentation studies. Data were analyzed descriptively using SPSS for quantitative and thematic analysis techniques were used for qualitative data analysis. Main Findings: The results of the study showed that the biology module integrating Qur'anic and hadith values ​​successfully improved students' academic understanding and religious character. The experimental group showed better results in understanding the theory of evolution and strengthening religious character compared to the control group. This module proved to be more effective in helping students understand the material of evolution and strengthening students' religious beliefs. Novelty/Originality of this study: This study offers a new approach in biology learning by integrating the values ​​of the Qur'an and hadith in the material of the theory of evolution. This not only deepens students' scientific understanding, but also strengthens their religious character. This study fills the gap in the literature that connects science and religion, and creates a holistic learning model in Islamic universities.